Antitumoral activity of L-ascorbic acid-poly-D,L-(lactide-co-glycolide) nanoparticles containing violacein - Dorival Martins (Dove Medical Press, 2010)
Dorival Martins1, Lucas Frungillo2, Maristela C Anazzetti2, Patrícia S Melo3, Nelson Durán11Institute of Chemistry, Biological Chemistry Laboratory, Universidade Estadual de Campinas-UNICAMP, C.P. 6154, CE P 13083-970, Campinas, SP, Brazil; 2Institute of Biology, Cell Cultures and Biopharmaceutical Laboratory, Universidade Estadual de Campinas, UNICAMP, Campinas, SP, Brazil; 3Campinas Integrated Metropolitan Faculties-METROCAMP, Campinas, SP, BrazilAbstract: It has been demonstrated that tumoral cells have a higher uptake of ascorbic acid compared to normal cells. This differential characteristic can be used as a way to improve the specificity of antitumoral compounds if combined with polymeric drug delivery systems. The aim of this study was to prepare, characterize and evaluate the antitumoral activity of poly-D,L-(lactide-co-glycolide) 50:50 loading the antitumoral compound violacein and capped with L-ascorbic acid. Nanoparticles were prepared using the nanoprecipitation method and morphologically characterized by scanning electron microscopy (SEM). The average diameter and Zeta potential were determined by photon correlation spectroscopy method (PCS), and assays were carried out to determine the content of ascorbic acid and in vitro drug release kinetics. The antitumoral activity of this system was also evaluated against HL-60 cells by tetrazolium reduction assay. Nanoparticles with size distribution between 300–400 nm and strong negative outer surface (-40 mV) were obtained by this method. Analysis of ascorbic acid content showed that this compound was mainly localized on the external surface of nanoparticles. Violacein loading efficiency was determined as 32% ± 1% and this drug was gradually released from nanoparticles at different rates depending on the composition of the release media. In addition, this system was observed to be 2 × more efficient as an antitumoral compared with free violacein.Keywords: violacein, ascorbic acid, nanoparticles, PLGA